Pelatihan Pengurangan Dampak Merkuri bagi Masyarakat Daerah Penambangan Emas Skala Kecil di Desa Sekotong Kabapuaten Lombok Barat - Seto Priyambodo; Basuki Rahmat; Gede Wira Buanayudha; Ida Ayu Eka Widiastuti; Lina Nurbaiti (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The purpose of this service activity is to reduce the impact of mercury on small-scale gold mining communities through training and coaching activities in Sekotong village. The Sekotong region, West Lombok Regency is an area rich in potential gold resources with the potential to mine 1,596 tons of gold and can be mined for decades. This potential has been exploited by the community by traditional gold mining. The gold mining area in Sekotong is spread over 3 locations, namely Buwun Mas, Kerato and Pelangan involving 5000 traditional miners. Gold processing carried out in the community is by using amalgamation and cyanidation methods. The technology provided in this service activity is by eliminating the use of mercury in gold processing, reducing the use of cyanide, training and coaching on appropriate standard operating procedures in handling mercury and cyanide, and processing cyanide before it is discharged into the environment. The result of this community service activity is that with the application of this technology, the environment and traditional gold miners become safer and healthier.